Harmonization of Exceptions to The Non-Retroctive Principle Between Positive Criminal Law and Islamic Law From Perspective of Maslahah Mursalah - Johar, Rama Dhini Permasari; Desvia, Lusiana (Jurnal El-Thawalib, 2025)
General criminal and Islamic criminal law each adhere to the precept of non-retroactivity. but, one of the interesting matters is that there are still exceptions to this non-retroactive principle in each general criminal regulation and Islamic criminal regulation. So the author is very inquisitive about discussing similarly the exceptions to the non-retroactive precept. aside from that, it is also interesting to review the problem aspect of establishing this exception. This targets to better know and understand the reasons and knowledge of the exception to this precept. The sort of studies that the writer carried out became library studies with a qualitative method. The statistics resources in this have a look at are associated documents, particularly the criminal Code, literature in the form of magazine articles inside the Google scholar database, and others. The information collection approach used is purposive sampling. The information analysis technique utilized by the author is content analysis.  The effects of this studies monitor that exceptions to the non-retroactive principle in general criminal regulation and Islamic criminal regulation are very suitable and have fantastic blessings while viewed from the maslahah issue due to the fact they involve the benefit of many people/preferred benefit.